1998
DOI: 10.2807/esm.03.11.00086-en
|View full text |Cite
|
Sign up to set email alerts
|

ESEN : a comparison of vaccination programmes Part two : pertussis

Abstract: This article is the second of a series of three, which compare vaccination programmes, immunisation schedules, vaccine coverage, and the epidemiological impact of vaccination for diphtheria, pertussis, measles, mumps, and rubella in eight countries (Denma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Interestingly, this cellular response was typically Th1 (28,29). In adults with no record of pertussis, we have recently found that 80 to 100% of individuals tested were CMI ϩ to B. pertussis antigens, including PT (5,27), a percentage hardly attributable to the coverage level of pertussis vaccination in Italy (17,27). The cytokine profile induced in purified T cells by B. pertussis antigens was essentially Th1 (5).…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, this cellular response was typically Th1 (28,29). In adults with no record of pertussis, we have recently found that 80 to 100% of individuals tested were CMI ϩ to B. pertussis antigens, including PT (5,27), a percentage hardly attributable to the coverage level of pertussis vaccination in Italy (17,27). The cytokine profile induced in purified T cells by B. pertussis antigens was essentially Th1 (5).…”
Section: Discussionmentioning
confidence: 96%
“…Since then, no evidence of major nationwide outbreaks of pertussis has been observed. In 1995 and 1996, 63% of cases were isolated from teenagers [84]. Analysis of the Finnish isolates revealed that all strains isolated between 1953 and 1964 contained ptxS1B.…”
Section: Finlandmentioning
confidence: 97%
“…Surveillance practice including pertussis case definitions, historical vaccine coverage and the number of pertussis cases reported by age group were collected. Some results have previously been reported [10]. Countries were divided into two groups [' high coverage ' (>90%) and 'low coverage ' (<90 %)] based on mean reported coverage in the 15-20 years prior to the serosurvey.…”
Section: Vaccine Programme History and Performancementioning
confidence: 99%
“…the United Kingdom) [8]. These events stimulated the development of acellular vaccines, specific subcomponents of the bacterium with a better side-effect profile [9], that several countries have now introduced [10,11].…”
Section: Introductionmentioning
confidence: 99%